Multilinear Fractional Integrals and Commutators on Generalized Herz Spaces (Analysis in Theory and Applications, 2016)
Suppose $\vec{b}=(b_1,…,b_m)\in (BMO)^m,$ $ I_{α,m}^{{Π b}}$ is the iterated commutator of $\vec{b}$ and the $m$-linear multilinear fractional integral operator $I_{α,m}$. The purpose of this paper is to discuss the boundedness properties of $I_{α,m}$ and $I_{α,m}^{{Π b}}$ on generalized Herz spaces with general Muckenhoupt weights.